Partial Tears of the Pectoralis Major Muscle - Strafun, S.S.; Haiovych, V.V.; Kulyk, Yu.A.; Lieskov, V.H. (TERRA ORTHOPAEDICA, 2020)
Summary. Partial tear of the pectoralis major muscle (PMM) is an extremely rare injury, but it needs to be studied. Objective: to carry out a comparative analysis of the clinic, diagnosis and treatment of patients with complete and partial tears of the PMM. Materials and Methods. A retrospective analysis of 9 patients with partial tears of the PMM who underwent surgical and conservative treatment at the Department of Microsurgery and Reconstructive Surgery of Upper Extremity of the SI “Institute of Traumatology and Orthopedics of NAMS of Ukraine” (Kyiv) from 2008 to 2018 was performed. The mean age of patients with partial tear of the PMM was 37.4±10.8 years (16 to 42 years); 8 were males and 1 was female. The follow-up period after surgical or conservative treatment was 12±2.8 months. The greatest number of injuries occurred during the bench press exercises – 55.6% (5 patients); on the uneven bars – 22.2% (2 patients) and in everyday life – 22.2% (2 patients). Results. Follow-up examination revealed that 55.6% (5 patients) had injuries of tendon-muscle transition IIC, 33.3% (3 patients) – of tendon part II D, and 11.1% (1 patient) – of muscle II B according to the Cordasco 2020 classification. All the patients deny taking steroids to increase muscle mass. Surgical treatment was performed within 10-643 days after the injury. Two operated on patients had acute injuries (up to 8 weeks after the trauma), and 3 had chronic injuries (more than 8 weeks after the trauma). The results on both the Quick DASH scale and the Subjective Evaluation of Patients with Pectoralis Major Muscle Injuries Questionnaire were negative in both groups during initial treatment. One year after the treatment, excellent and good results were observed in the operated on group; the conservative group showed unsatisfactory results. We did not note any complications after surgical interventions in operated on group of patients. Conclusions. Partial tears of the PMM require more careful differentiation and additional examination methods. Physically active patients with isolated tears of the PMM need surgical treatment. Such treatment gives excellent and good results, while conservative treatment – unsatisfactory. Due to the small number of patients in our study, partial PMM tears require further investigation.